Phytochemical profile, proximate composition and anti-oxidant properties Flueggea leucopyrus (Willd), a plant used as complementary and alternative medicine by cancer patients in Sri Lanka - Bulugahapitiya, V. P.; Munasinghe, A. A. M. B. (My University, 2020)
Flueggea leucopyrus Willd (Phylanthreceae), locally known as “katupila”, a plant has been known with vast applications in traditional medicine, and recently it has been widely used in the treatment of cancers in complementary and alternative medicine in Sri Lanka. Though chemical investigation of this plant has been carried out in other countries, no detailed study on phytochemical, proximate and anti-oxidant properties reported in Sri Lanka on this plant. In this study, methanolic extract of leaves of F.leucopyrus was prepared using maceration and tested for phytochemicals and proximate composition using standard procedures described in the literature. Phytochemical screening revealed the presence of alkaloids, terpenoids, unsaturated sterols, glycosides, saponins, phenolics, flavonoids and tannins. Gravimetric methods were used to quantify alkaloids and saponins, and they were found as 0.13±0.00 % g and 0.74±0.01 % g respectively. Colorimetric methods were used to quantify tannins, total phenolics and total flavonoids contents and results obtained were 1.15±0.01 Tannic Acid Equivalent, 38.49±0.30 mg/g Gallic Acid Equivalent and 11.48±0.27 mg/g Quercetin equivalent respectively. Proximate composition was found to be 10.20 g/100 g, 7.06 g/100 g, 1.50 g/100 g , 8.44 g/100 g, 21.20g/100g and 48.73 for moisture, ash, lipids, fiber, protein and carbohydrates contents respectively. Main elements in the leaves were found as N:3.39±0.05, Na:0.37±0.24, K:0.36±0.01 and P:0.01±0.00 in g/100g. Anti-oxidant capacity was evaluated using DPPH and FRAP assays and plant showed great anti-oxidant capacity giving IC50 value of 402.58±3.97 µg/mL in DPPH assay and 148.65±11.91 µg/mL of FRAP value. As conclusion, this study gives the broad picture on phytochemical, proximate and major elements content, and anti-oxidant capacity of leaves proving the highly medicinal value of the plant.
Keywords: Fluegea leucopyrus; Phytochemicals; proximate compositions; anti-oxidant; DPPH assay; FRAP assay